Human Pericytes for Ischemic Heart Repair123. (12th February 2013) - Chen, Chien‐Wen; Okada, Masaho; Proto, Jonathan D.; Gao, Xueqin; Sekiya, Naosumi; Beckman, Sarah A.; Corselli, Mirko; Crisan, Mihaela; Saparov, Arman; Tobita, Kimimasa; Péault, Bruno; Huard, Johnny
Abstract Human microvascular pericytes (CD146+/34−/45−/56−) contain multipotent precursors and repair/regenerate defective tissues, notably skeletal muscle. However, their ability to repair the ischemic heart remains unknown. We investigated the therapeutic potential of human pericytes, purified from skeletal muscle, for treating ischemic heart disease and mediating associated repair mechanisms in mice. Echocardiography revealed that pericyte transplantation attenuated left ventricular dilatation and significantly improved cardiac contractility, superior to CD56+ myogenic progenitor transplantation, in acutely infarcted mouse hearts. Pericyte treatment substantially reduced myocardial fibrosis and significantly diminished infiltration of host inflammatory cells at the infarct site. Hypoxic pericyte‐conditioned medium suppressed murine fibroblast proliferation and inhibited macrophage proliferation in vitro. High expression by pericytes of immunoregulatory molecules, including interleukin‐6, leukemia inhibitory factor, cyclooxygenase‐2, and heme oxygenase‐1, was sustained under hypoxia, except for monocyte chemotactic protein‐1. Host angiogenesis was significantly increased. Pericytes supported microvascular structures in vivo and formed capillary‐like networks with/without endothelial cells in three‐dimensional cocultures. Under hypoxia, pericytes dramatically increased expression of vascular endothelial growth factor‐A, platelet‐derived growth factor‐β, transforming growth factor‐β1 and corresponding receptors while expression of basic fibroblast growth factor, hepatocyte growth factor, epidermal growth factor, and angiopoietin‐1 was repressed. The capacity of pericytes to differentiate into and/or fuse with cardiac cells was revealed by green fluorescence protein labeling, although to a minor extent. In conclusion, intramyocardial transplantation of purified human pericytes promotes functional and structural recovery, attributable to multiple mechanisms involving paracrine effects and cellular interactions. STEM CELLS2013;31:305–316